Targeting Schizophrenia: A Review of Pharmacological and Psychosocial Innovations - Janicka, Urszula; Bogdan, Klaudia; Jankowski, Mikołaj; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria; Olszówka, Magdalena; Dziugieł, Sonia (Quality in Sport, 2026)
Background. Paranoid schizophrenia is the most common subtype of schizophrenia, characterized by both positive symptoms, such as hallucinations and delusions, and negative symptoms like reduced motivation and social withdrawal. While pharmacological advances have improved symptom control, challenges remain in treating negative symptoms and ensuring long-term adherence and recovery. Aim of the study. This review analyzes recent literature (2020–2025) on pharmacological and psychosocial treatment strategies for paranoid schizophrenia, with attention to effectiveness, tolerability, and integration. Materials and methods. PubMed and Google Scholar were searched for meta-analyses, RCTs, and guidelines published in the last 5 years using terms like “paranoid schizophrenia”, “antipsychotics”, “long-acting injectables”, “CBT”, “treatment”. Current stage of knowledge. Modern antipsychotics, particularly SGAs and LAIs, reduce relapse risk and enhance adherence. Cariprazine and newer agents like Cobenfy show promise in treating negative and treatment-resistant cases. Integration with psychosocial strategies—especially CBT and family interventions—enhances functional recovery, though results for negative symptoms remain mixed. Novel treatments target glutamatergic and cholinergic systems beyond traditional dopaminergic focus. Conclusions. A multimodal approach is essential. Future treatment should emphasize personalized strategies, early intervention, targeting of non-dopaminergic pathways, and better access to integrated care, particularly for patients with persistent negative or cognitive symptoms.